Economic and Social Impact of the COVID-19 Pandemic on Small Business from the Republic of Moldova - Lica ERHAN; Ludmila COBZARI; Liliana STAVER (Communications of International Proceedings, 2022)
The Covid-19 came with major challenges for the whole world. First, it threatens millions of people’s lives all over the world. Second, it threatens businesses activity and is leaving a huge impact on the economy and the society. The pandemic crisis affected small and medium-sized business more than the large one, because they were more vulnerable and least prepared to face the economic crisis. Over the last decades, SMEs have become one of the most important sectors of economy in many countries. Similar to other countries, SMEs represent the majority of businesses in the Republic of Moldova, but Covid-19 is not the only difficulty the small business sector from Moldova is facing, this sector is being hit also by several internal and external shocks. Starting from this reality, the primary aim of this research paper is to evaluate the economic and social impact of the coronavirus on small and medium-sized businesses in the Republic of Moldova. A secondary aim of the research is to develop recommendations that will help SMEs from the Republic of Moldova to overcome the crisis. In order to meet the aims and objectives of the research project, an analysis of secondary data resources will be carried out, using scientific methods, in particular logical methods, such as comparative analysis, synthesis, induction and deduction. The research will include a macro analysis of SMEs from Republic of Moldova, measuring pre-pandemic and pandemic values, based on official data from national and international bodies. The research will also, include the results from the most recent surveys and will be completed by the most recent data and references in this field of research and own reflections of the authors. The results of this research paper will make it possible to develop recommendations for improving the overall results of SMEs from the Republic of Moldova.
Keywords: Covid-19; SMEs; economic and social effects.